2013
DOI: 10.1038/nature12207
|View full text |Cite
|
Sign up to set email alerts
|

EndMT contributes to the onset and progression of cerebral cavernous malformations

Abstract: Cerebral cavernous malformation (CCM) is a vascular dysplasia, mainly localized within the brain and affecting up to 0.5% of the human population. CCM lesions are formed by enlarged and irregular blood vessels that often result in cerebral haemorrhages. CCM is caused by loss-of-function mutations in one of three genes, namely CCM1 (also known as KRIT1), CCM2 (OSM) and CCM3 (PDCD10), and occurs in both sporadic and familial forms. Recent studies have investigated the cause of vascular dysplasia and fragility in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
442
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 415 publications
(470 citation statements)
references
References 35 publications
18
442
2
1
Order By: Relevance
“…Indeed, although TGFβ is one of the most potent inducers of EMT (14), the role of BMPs is still not completely clear (25). BMPs have been described as either inhibitors of endMT (BMP7 in cardiac fibrosis) (26) or inducers of endMT [BMP6 in cerebral cavernous malformations (27) and BMP2 in cardiac valve formation (28)]. BMP9 has been recently shown to induce EMT in hepatocellular carcinoma cells (29), and our data support that BMP9 and BMP10 can also induce endMT.…”
Section: Discussionsupporting
confidence: 69%
“…Indeed, although TGFβ is one of the most potent inducers of EMT (14), the role of BMPs is still not completely clear (25). BMPs have been described as either inhibitors of endMT (BMP7 in cardiac fibrosis) (26) or inducers of endMT [BMP6 in cerebral cavernous malformations (27) and BMP2 in cardiac valve formation (28)]. BMP9 has been recently shown to induce EMT in hepatocellular carcinoma cells (29), and our data support that BMP9 and BMP10 can also induce endMT.…”
Section: Discussionsupporting
confidence: 69%
“…CCM1'in fonksiyonel kaybı, Notch sinyal iletimini hasara uğratmakta ve oluşan bu hasar durumu da BMP6 (kemik morfojenik proteini 6) miktarında artışla ortaya çıkmaktadır. BMP6'nın hücrede artışı, TGF-ß (transforme edici büyüme faktörü ß) molekülünü ve BMP sinyal yolağını aktive eder ve endotelyal mezenşimal dönüşümün artmasını tetiklemektedir (28).…”
Section: Ccm1'in Endotelyal Mezenşimal Geçişteki Olası Rolleriunclassified
“…109,110 By use of an endothelial-specific tamoxifeninducible Ccm1 loss of function mice (iCCM1), it was demonstrated that the endothelial cells lining the vascular lesions associated with CCM, showed highly disorganized VE-cadherin expression and upregulated N-cadherin expression. 111 Furthermore, CCM1 downregulation in lung and brain microvascular endothelial cells showed increased proliferation and enhanced invasive/ sprouting capacitiy, which is mediated by Notch inhibition and subsequent BMP6 (bone morphogenetic protein 6) upregulation. Upregulation of BMP6 activates transforming growth factor-β (TGF-β) and BMP signaling pathways and results in increased EndMT.…”
Section: Ccm In Cell Polaritymentioning
confidence: 99%
“…Upregulation of BMP6 activates transforming growth factor-β (TGF-β) and BMP signaling pathways and results in increased EndMT. 111 As Wnt/β-catenin signaling plays an important role in EndMT in myocardial cells 112 and loss of CCM1 enhances β-catenin-dependent activation of the Wnt signaling pathway, 68 this might be another pathway that contributes the EndMT phenotype.…”
Section: Ccm In Cell Polaritymentioning
confidence: 99%